PESANTREN (DARI DULU) SIAP UNTUK ASEAN ECONOMIC COMMUNITY (AEC) 2016 PESANTREN READY FOR ASEAN ECONOMIC COMMUNITY 2016 - Usman Abu Bakar (Jurnal Ilmiah Pesantren, 2017)
The research is the study of adaptation values of boarding school to be students’ hostel towards the Asean Economic Community (AEC). Basic problem which become this problem of academic assessment is the gap between demand and supply of human resources caused by 2030 Indonesia will need a workforce with high competence and a medium amount of 113 million workers, and eventually Indonesia will be minus 9 million workers. So what about the boarding schools? Does he still dwell on old paradigms and perceptions, which states that schools are religious education and not science education (general). Do schools educate people who are ready globally? Education is an important institution for the setup process and improving the quality of human resources. This indicates the principles of quality in it. So, we need education innovation in the broadest sense continuously and systematically. Some strategic issues include obstacles that can be used as a foothold for Islamic educational institutions to innovate, first, the quality of education is still low and high dropout rates. Second, has not exploited its full potential for the advancement of science and technology education due to lack of awareness and mastery of technology education actors. Third, the culture of learning in the community has not developed. Fourth, professionalism and welfare educators are not in accordance with the challenge of improving the quality. Fifth, declining health and nutritional status as a result of economic development. And sixth, symptoms of declining morals, manners, and tolerance among learners.The concept of student dormitories to be formed in this discussion is a hostel for students not to abandon the principles of the demands of competence and professionalism in line with the Asean Economic Community (AEC) or the Asean Economic Community (AEC), which has also been prepared by the government through various regulations. Islam-based education is not born solely of science and technology, they are born with the basic sciences as an educational framework to ensure that education is not free from the runway faith, the Shari’a and Islamic morals.